Team players and teamwork : the new competitive business strategy - Parker, Glenn M., 1938- 4 0 16; 5 (San Francisco, California : Jossey-Bass Publishers, 1996)
Discusses the benefits of teams and teamwork within the corporate culture, describing four styles of team players, and examining team-driven organizations such as Xerox, Honeywell, General Motors, 3M, and others.
Includes bibliographical references and index.
Adult.
Keywords: 2 -- 0; 6; Teams in the workplace.;Corporate culture. -- 20; 20; 2